Digital codicology : medieval books and modern labor - Whearty, Bridget (Text technologies., 2022)
"Medieval manuscripts are our shared inheritance, and today they are more accessible than ever thanks to digital copies online. Yet for all that widespread digitization has fundamentally transformed how we connect with the medieval past, we understand very little about what these digital objects really are. We rarely consider how they are made or who makes them. This case-study rich book demystifies digitization, revealing what it's like to remake medieval books online and connecting modern digital manuscripts to their much longer media history, from print, to photography, to the rise of the internet. Examining classic late-1990s projects like "Digital Scriptorium 1.0" alongside late-2010s initiatives like "Bibliotheca Philadelphiensis," and world-famous projects created by the British Library, Corpus Christi College Cambridge, Stanford University, and the Walters Art Museum against in-house digitizations performed in lesser-studied libraries, Whearty tells never-before-published narratives about globally important digital manuscript archives. Drawing together medieval literature, manuscript studies, digital humanities, and imaging sciences, Whearty shines a spotlight on the hidden expert labor responsible for today's revolutionary digital access to medieval culture. Ultimately, this book argues that centering the modern labor and laborers at the heart of digital cultural heritage fosters a more just and more rigorous future for medieval, manuscript, and media studies"--